2022
DOI: 10.1088/1361-6528/ac8c9b
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the mass sensitivity of graphene resonators via kirigami

Abstract: The unique mechanical properties of graphene make it an excellent candidate for resonators. We have used molecule dynamic to simulate the resonance process of graphene. The kirigami approach was introduced to improve the mass sensitivity of graphene sheets. Three geometric parameters governing the resonant frequency and mass sensitivity of Kirigami graphene NEMS were defined. The simulation results demonstrate that the closer the Kirigami defect is to the central position of the drum graphene, the higher the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…Also, graphene has an ultrahigh thermal conductivity , and fatigue life, which combined with its high Young’s modulus, , low mass density, , and large surface area make graphene a strong candidate for resonant sensors . Since the first realization of graphene mechanical resonators by Bunch et al, many experimental , and theoretical studies have shown that graphene resonators promise to be ultrasensitive detectors of force, mass, and charge …”
Section: Introductionmentioning
confidence: 99%
“…Also, graphene has an ultrahigh thermal conductivity , and fatigue life, which combined with its high Young’s modulus, , low mass density, , and large surface area make graphene a strong candidate for resonant sensors . Since the first realization of graphene mechanical resonators by Bunch et al, many experimental , and theoretical studies have shown that graphene resonators promise to be ultrasensitive detectors of force, mass, and charge …”
Section: Introductionmentioning
confidence: 99%